Structural evolution study by solid-state NMR of photopolymerizable aluminophosphosilicate hybrid materials - Costa, Beatriz Helena [UNESP]; Tayama, Gabriel Toshiaki; Santagneli, Silvia Helena [UNESP] (Elsevier, 2024)
Aluminophosphosilicate materials of composition (mol.%) xSiO2[(Al2O3)50–(P2O5)50]100-x were prepared through sol-gel method and heat-treated yielding non-crystalline materials. The structural evolution from the hybrid to heat-treated material as a function of the SiO2 content was studied by 13C, 29Si, 31P and 27Al solid-state NMR, infrared spectroscopies, X-ray diffraction and differential scanning calorimetry (DSC). NMR analyses showed the AlPO4 formation in the matrix and heterocondensation, forming Al-O-P and P-O-Si linkages. The heat treatment promoted the formation of a more interconnected SiO2 tetrahedra network as the SiO2 content increased. Similar to the hybrid materials, the increase of SiO2 content induces the replacement of P-O-Al(IV) bonds by Si-O-Al(IV) bonds in the heat-treated materials as confirmed by 27Al NMR and 27Al{31P} REDOR data, which was also supported by Raman analysis. This sol-gel route provides a novel way to fabricate new homogeneous materials, which can be doped with rare earths and applied to new optical devices.
Keywords: Aluminophosphosilicate hybrid material; Sol-gel; Solid-state NMR